1994
DOI: 10.1007/bf00028858
|View full text |Cite
|
Sign up to set email alerts
|

Avenacosidase from oat: purification, sequence analysis and biochemical characterization of a new member of the BGA family of ?-glucosidases

Abstract: A protein consisting of 60 kDa subunits (As-P60) was isolated from etiolated oat seedlings (Avena sativa L.) and characterized as avenacosidase, a beta-glucosidase that belongs to a preformed defence system of oat against fungal infection. The enzyme is highly aggregated; it consists of 300-350 kDa aggregates and multimers thereof. Dissociation by freezing/thawing leads to complete loss of enzyme activity. The specificity of the enzyme was investigated with para-nitrophenyl derivatives which serve as substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 35 publications
4
33
0
Order By: Relevance
“…LPH is synthesized as a single-chain 215-245 kDa precursor comprising four tandemly repeated domains [2][3][4][5][6][7][8]. These show sequence similarity with the type 1 family of glycosyl hydrolases (T1GH family), a family of proteins that includes single-domain enzymes present in micro-organisms (see [9,10] and references therein] and plants [11][12][13], and in the liver of mammals [14]. The T1GH family also comprises multi-domain proteins expressed in the intestine of non-mammalian vertebrates and in invertebrates, but their sequences have not been fully determined [15].…”
Section: Introductionmentioning
confidence: 99%
“…LPH is synthesized as a single-chain 215-245 kDa precursor comprising four tandemly repeated domains [2][3][4][5][6][7][8]. These show sequence similarity with the type 1 family of glycosyl hydrolases (T1GH family), a family of proteins that includes single-domain enzymes present in micro-organisms (see [9,10] and references therein] and plants [11][12][13], and in the liver of mammals [14]. The T1GH family also comprises multi-domain proteins expressed in the intestine of non-mammalian vertebrates and in invertebrates, but their sequences have not been fully determined [15].…”
Section: Introductionmentioning
confidence: 99%
“…The BGA family includes bacterial ~-glucosidases, archaebacterial I~-galactosidase, plant thioglucosidases, and human lactase-phlorizin hydrolase, while the BGB family includes fungal and rumen bacterial I~-glucosidases [18,21]. All of the seven plant I~-glucosidases encoded by the cDNAs which have been cloned so far were found to belong to the BGA family [18,[22][23][24][25][26]. The BGA family enzymes are predicted to share a common mechanism of enzymatic hydrolysis of 13-…”
Section: Resultsmentioning
confidence: 99%
“…Gus-Maier et al reported the purification of a protein termed As-P60 from oat leaves and its cDNA cloning [22,34]. As-P60 was identified as avenacosidase, which is responsible for the catabolism of oat saponins, by immunological evidences [22,34].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it is known that saponins such as avenacosides in oat are activated by the plant's enzymes in response to tissue damages or pathogen attacks. 22) Thus, most of saponins may be considered a part of plants' defense systems and have been included in a large group of protective molecules found in plants named 'phytoanticipins' or 'phytoprotectants'. 23) However, we found in the present study that GTS helps C. elegans survive normally rather than does harm to them, since GTS supplement supports worm egg laying, growth, and development and extended life span in spite of cholesterol deprivation.…”
Section: Discussionmentioning
confidence: 99%